1999
DOI: 10.1083/jcb.147.7.1443
|View full text |Cite
|
Sign up to set email alerts
|

Export of a Cysteine-Free Misfolded Secretory Protein from the Endoplasmic Reticulum for Degradation Requires Interaction with Protein Disulfide Isomerase

Abstract: Protein disulfide isomerase (PDI) interacts with secretory proteins, irrespective of their thiol content, late during translocation into the ER; thus, PDI may be part of the quality control machinery in the ER. We used yeast pdi1 mutants with deletions in the putative peptide binding region of the molecule to investigate its role in the recognition of misfolded secretory proteins in the ER and their export to the cytosol for degradation. Our pdi1 deletion mutants are deficient in the export of a misfolded cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 65 publications
5
143
2
1
Order By: Relevance
“…This suggests that Pdi1 mediates reduction of disulphide in yeast in the absence of a mammalian ERdj5 ortholog. 45 In plants, PDI may perform the disulphide bond reduction role for ERAD substrates. Alternatively, plant ERdj3A, which has a TRX domain, may act as a reductase in a similar manner to ERdj5.…”
Section: Perspectivesmentioning
confidence: 99%
“…This suggests that Pdi1 mediates reduction of disulphide in yeast in the absence of a mammalian ERdj5 ortholog. 45 In plants, PDI may perform the disulphide bond reduction role for ERAD substrates. Alternatively, plant ERdj3A, which has a TRX domain, may act as a reductase in a similar manner to ERdj5.…”
Section: Perspectivesmentioning
confidence: 99%
“…We have shown that deletion of 25 amino acids of the yeast PDI bЈ domain results in decreased glycosylation acceptor peptide binding (Pdi ⌬252-277; 40% peptide binding of wild type; ref. 25), and that deletion of the amino-terminal half of the bЈ domain and a small proportion of the preceding b domain reduces peptide binding to PDI to background levels (Pdi ⌬222-302; ref. 25).…”
Section: Release From Pdi Is Not Critical For Glycopeptide Export Fromentioning
confidence: 99%
“…Cells were radiolabeled and lysed, and proteins were immunoprecipitated or precipitated with concanavalin A (ConA)-Sepharose as in described by Gillece et al (1999). Lectin-precipitated samples were eluted with 1 M ␣-methyl mannoside in 20 mM Tris-HCl, pH7.5, 150 mM NaCl, 2 mM EDTA for 1 h at 30°C.…”
Section: Pulse-chase Experimentsmentioning
confidence: 99%